Analysis of The Effect of Service Quality and Product Quality on Consumer Loyalty - D. Purnomo; Dingot Hamonangan Ismail; Verus Hardian (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The purpose of this study is to obtain valid and reliable empirical data, facts, and information regarding the analysis of product quality factors and customer loyalty service quality of fast food restaurant consumers. This research is a quantitative research. There are two independent variables, namely product quality (X1), Service Quality (X2) and one dependent variable, namely Consumer Loyalty (Y). Data was collected by means of a survey. The data analysis technique used multiple linear regression analysis. The population in this study were all consumers who had bought fast food using an online application, where there were 142 respondents who gave answers to questionnaires via google forms which were distributed online. The results showed that there was an effect of service quality on customer loyalty, amounting to 51.9.%, there was an effect of product quality on customer loyalty of 59.8% and there was an effect of service quality and product quality together in influencing consumer loyalty by 61, 5%.